1999
DOI: 10.4314/acsj.v7i4.27736
|View full text |Cite
|
Sign up to set email alerts
|

Use of wheat straw, soybean trash and nitrogen fertiliser for maize production in the Kenyan highlands

Abstract: Making best use of available crop residues is an important component of integrated nutrient management. A field study was conducted over two seasons (1997 and 1998) in Kenya that examined use of wheat straw, soybean trash and nitrogen fertiliser as nutrient inputs for maize (Zea mays L.) production. The organic inputs were applied at the rate of 2 t ha-1 per season and urea was added at rates of 0, 20, 40, 80 and 100 kg N ha-1 in an incomplete factorial treatment structure that also included a complete control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Application of organic amendments under conservation tillage systems is expected to provide a long-term source of N and reduce the need for N fertilization. In western Kenya, incorporation of crop residues (maize stover, wheat straw, bean trash and improved fallows) into soils have been associated with improved N levels in soils and subsequent high maize and bean yields (Palm et al 1997;Okalebo et al 1999;Kifuko 2002;Ndung'u et al 2006;Waigwa 2002). Cropping systems had no significant effect on total N content in all cropping seasons.…”
Section: Effects Of Residue Application and Fertilizer N Addition On mentioning
confidence: 95%
“…Application of organic amendments under conservation tillage systems is expected to provide a long-term source of N and reduce the need for N fertilization. In western Kenya, incorporation of crop residues (maize stover, wheat straw, bean trash and improved fallows) into soils have been associated with improved N levels in soils and subsequent high maize and bean yields (Palm et al 1997;Okalebo et al 1999;Kifuko 2002;Ndung'u et al 2006;Waigwa 2002). Cropping systems had no significant effect on total N content in all cropping seasons.…”
Section: Effects Of Residue Application and Fertilizer N Addition On mentioning
confidence: 95%
“…Table 7. Effect of continued application of crop residues and nitrogen fertilizer on maize grain yield (t/ha) in a Chepkoilel ferralsol, Eldoret, Kenya (after Okalebo et al 1999 particularly when soil moisture was adequate and from addition of organic inputs higher in mineralisable nutrients. These findings suggest that better use may be made of crop residues than the burning following harvest as is it currently practiced by many farmers in this wheat growing area of western Kenya .…”
Section: Crop Responses To Inorganic Resourcesmentioning
confidence: 99%
“…Nutrient depletion, coupled with the inability of farmers to apply inorganic fertilizers and the practices of grazing and burning plant residues, has been indicated as the major cause of declining agricultural production in Africa (Kikafunda et al, 2001; Sanchez et al, 1997). Several studies in tropical regions have shown that application of grain legume residues, such as chickpea, Hyacinth bean ( Dolichos lablab L.), soybean ( Glycine max ), and tropical forage legumes, increased soil N content (Njunie et al, 2004; Okalebo et al, 1999; Onwonga 1997). In previous studies, no attempt was made to test the mature chickpea and green manure and to relate their measured residue parameters with N dynamics in soil.…”
Section: Discussionmentioning
confidence: 99%
“…Onwonga (1997) reported that mature chickpea residue could return 54 kg N ha −1 when the DM yield was 1.7 Mg ha −1 , which is equivalent to a fertilizer replacement value of 38 kg N ha −1 for wheat. Okalebo et al (1999) reported higher maize yields after application of soybean residues.…”
mentioning
confidence: 97%